Optical thermal imaging for breast cancer diagnosis - Zubir, Nazira; Pushpanathan, K; Mat Noor, N.A (International Journal of Engineering Inventions, 2016)
Breast cancer has become the most common cancer in women. Fatality could be due to the delay in the intervention and detection of cancer. Mammography, Computated Tomography (CT) scan, Magnetic Resonance Imaging (MRI) and ultrasound are examples of imaging modalities for cancer screening. Nonetheless, considerable demand from the patients for non-invasive, low price, no compression and no ionization have led to the consideration for optical thermal imaging for breast cancer diagnosis. Overdiagnosis and overtreatment using mammography further aided in development of thermal imaging. The fundamental principle of optical thermal imaging relies on physiology such as the distribution of temperature on the skin surface. This article highlights the potential usage of optical thermal imaging, its limitations, advantages and latest concerns pertaining the usage. One of the suggestions is the usage of optical thermal imaging as adjunctive tool to mammography in breast cancer diagnosis. Novel attempts in thermography are also discussed for instance the emerging of rotational thermography replacing the conventional thermography.